Positive electrode additive of lithium ion battery, preparation method of positive electrode additive, positive electrode plate and lithium ion battery
Through the ionic liquid-coated positive electrode additives of ferroelectric materials, the performance differences of composite positive electrode materials during processing are solved, the ratio, circulation and high temperature performance of lithium-ion batteries are improved, and the uniform charge distribution and stable migration of positive electrode materials are achieved. ability.
Patent Information
- Application Number
- CN202411509314.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-26
- Publication Date
- 2024-12-13
AI Technical Summary
Composite positive electrode materials show poor processing performance during pulping, coating and rolling. The migration and diffusion abilities of lithium ions in different positive electrode materials are different, resulting in uneven charge distribution, metal ions precipitation, and reducing lithium ion batteries. rate performance, cycle stability and high temperature performance.
The ferroelectric material coated with ionic liquid is used as the positive electrode additive, and mixed evenly through the rotary reactor to form a gel-like precipitate and dry it. The obtained positive electrode additive can promote the dispersion of particles of positive electrode materials of different properties in the composite positive electrode material, and improve suspension stability. and compatibility, enhancing the migration and diffusion capabilities of lithium ions.
The dispersion and suspension stability of composite positive electrode materials are improved, the rate performance, cycle stability and high temperature performance of lithium-ion batteries are improved, metal ion precipitation is suppressed, and the processability and output performance of the positive electrode sheet is improved.
Smart Images

Figure CN119133457A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a positive electrode additive for a lithium-ion battery and a preparation method thereof, a positive electrode sheet, and a lithium-ion battery. Background Art
[0002] In recent years, the research and development direction of lithium-ion batteries has gradually shifted from single performance optimization to coordinated improvement of overall performance. Studies have shown that the mono- / binary composite cathode materials prepared by combining single cathode materials with other non-cathode materials or cathode materials can achieve complementary advantages, improve the electrochemical performance and cycle stability of the battery, and further reduce the cost of raw materials while maintaining or improving performance, which has very considerable application value.
[0003] However, the practical application of composite cathode materials still faces many challenges. Due to the significant differences in particle size, density and surface state of different material components of composite cathode materials, composite cathode materials show poor processing performance in the preparation of cathode sheets such as slurrying, coating and rolling. In addition, the migration and diffusion capabilities of lithium ions in different cathode materials of lithium-ion batteries are different, resulting in the inability of lithium ions to move quickly in different cathode materials, uneven charge distribution on the surface of the cathode active material of lithium-ion batteries, and easy precipitation of metal ions, which reduces the rate performance, cycle stability and high temperature performance of lithium-ion batteries. Summary of the invention
[0004] In order to solve or partially solve the problems existing in the related art, the present application provides a positive electrode additive for a lithium ion battery and a preparation method thereof, a positive electrode plate, and a lithium ion battery, which can improve the processability of the positive electrode slurry and the positive electrode plate of the lithium ion battery, and enhance the rate performance, cycle stability and high temperature performance of the lithium ion battery.
[0005] In a first aspect, the present application provides a positive electrode additive for a lithium ion battery, wherein the positive electrode additive comprises a ferroelectric material coated with an ionic liquid; wherein:
[0006] The mass ratio of the mass of the ferroelectric material to the mass of the ionic liquid is m1, 0.5≤m1≤100.
[0007] Preferably, the ferroelectric material includes BaTiO3 (barium titanate), (K, Na)NbO3, PbZrTiO3, (Bi 0.5 Na 0.5 )TiO3、Sr 1-x Ba x Nb2O6、NaBa2Nb5O 15 、Bi4Ti3O 12 、CaBi4Ti4O 15、SrBi4Ti4O 15 One or more of .
[0008] Preferably, the ionic liquid includes one or more of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.
[0009] Preferably, the imidazolium ionic liquid includes one or more of 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium fluoride, 1-butyl-3-methylimidazolium fluoride, 1-allyl-3-methylimidazolium chloride, and 1-octyl-3-methylimidazolium hexafluorophosphate.
[0010] A second aspect of the present application provides a method for preparing a positive electrode additive, the preparation method comprising:
[0011] Obtain ferroelectric materials and ionic liquids according to a set mass ratio;
[0012] The ferroelectric material and the ionic liquid are mixed uniformly in a rotating reactor according to set conditions to obtain a positive electrode additive for a lithium ion battery; wherein,
[0013] The positive electrode additive comprises a ferroelectric material coated with an ionic liquid, wherein the mass ratio of the mass of the ferroelectric material to the mass of the ionic liquid in the ferroelectric material coated with the ionic liquid is m1, and 0.5≤m1≤100.
[0014] Preferably, the set mass ratio is the mass ratio m2 of the mass of the ferroelectric material to the mass of the ionic liquid during the preparation of the positive electrode additive, and 0.1≤m2≤10.
[0015] Preferably, the step of uniformly mixing the ferroelectric material and the ionic liquid in a rotary reactor according to set conditions to obtain a positive electrode additive for a lithium ion battery comprises:
[0016] The ferroelectric material and the ionic liquid are uniformly mixed in a rotating reactor according to set conditions;
[0017] separating the uniformly mixed ferroelectric material and the excess ionic liquid in the ionic liquid to obtain a colloidal precipitate;
[0018] The colloidal precipitate is dried to obtain the positive electrode additive.
[0019] Preferably, the set conditions include mixing temperature T, and / or mixing time t; wherein,
[0020] 60℃≤T≤200℃;
[0021] 4h≤t≤48h.
[0022] A third aspect of the present application provides a positive electrode plate for a lithium-ion battery, wherein the positive electrode plate comprises the positive electrode additive as described above, or comprises the positive electrode additive prepared by the preparation method as described above.
[0023] Preferably, the mass of the positive electrode additive is 0.001wt%-10wt% of the mass of the positive electrode material in the positive electrode sheet;
[0024] Preferably, the mass of the positive electrode additive is 0.01wt%-2wt% of the mass of the positive electrode material in the positive electrode sheet.
[0025] A fourth aspect of the present application provides a lithium-ion battery, which includes the positive electrode plate as described above.
[0026] The technical solution provided by this application may have the following beneficial effects:
[0027] The technical solution of the present application is that the positive electrode plate of the lithium ion battery includes a positive electrode additive, and the positive electrode additive includes a ferroelectric material coated with an ionic liquid. The ferroelectric material has a spontaneous polarization characteristic, and its unique crystal structure makes the positive and negative charge centers not overlap, resulting in an electric polarization intensity that is not equal to zero. The electric polarization intensity will be enhanced under external pressure or electric field conditions, and positively charged and negatively charged dipole ends will be formed on two opposite surfaces of the ferroelectric material, respectively. The electrostatic repulsion can promote the dispersion of positive electrode material particles with different properties (particle size, density, specific surface area, etc.) in the composite positive electrode material of the lithium ion battery, and at the same time form a steric hindrance to effectively prevent the aggregation and sedimentation of positive electrode material particles with different properties; the ionic liquid is in a molten state at room temperature, has a uniform charge distribution, good thermal stability, and has good compatibility with positive electrode material particles with different properties in the positive electrode slurry, can improve the compatibility between the ferroelectric material and the positive electrode material particles with different properties, and improve the suspension stability of the positive electrode slurry through its viscosity. Therefore, the positive electrode additive of the lithium ion battery of the embodiment of the present application can improve and enhance the dispersibility, uniformity and suspension stability of the positive electrode material particles of different properties in the composite positive electrode material of the lithium ion battery in the composite positive electrode slurry, so as to meet the coating requirements and rolling process requirements of the subsequent positive electrode sheet, and improve the processability of the composite positive electrode slurry and the positive electrode sheet of the lithium ion battery. In addition, the ferroelectric material coated with the ionic liquid is extremely stable, and the positive electrode sheet can also have excellent and stable ion conduction ability under high temperature conditions; the built-in electric field generated by the polarization of the ferroelectric material can enhance the migration and diffusion ability of the lithium ions of the lithium ion battery between the positive electrode materials of different properties, and make the charge on the surface of the positive electrode active material evenly distributed, inhibit the precipitation of metal ions, and enhance the output performance of the lithium ion battery such as rate performance, cycle stability, safety and high temperature performance.
[0028] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0030] Figure 1 It is a schematic flow chart of the method for preparing the positive electrode additive shown in the embodiment of the present application. DETAILED DESCRIPTION
[0031] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0032] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0033] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0034] Lithium-ion batteries have become an important energy storage device in the field of modern electronic equipment and electric vehicles due to their high energy density, long cycle life and environmental friendliness. The positive electrode materials of lithium-ion batteries in related technologies mainly include lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2) and layered nickel-manganese-cobalt or nickel-cobalt-aluminum oxide (LiMO2, M=Ni x Co y Mn z / Al z , and x+y+z=1), etc. Although these positive electrode materials have their own advantages, they still have certain limitations in practical applications.
[0035] Specifically, the positive electrode material LiFePO4 has excellent structural stability and safety, is pollution-free and low in cost, but its tap density is low and its conductivity is poor, resulting in a low volume energy density of lithium-ion batteries and poor performance at high-rate charge and discharge. The positive electrode material LiCoO2 has a high capacity and energy density, but has obvious disadvantages in terms of cycle life, thermal stability and cost, and due to the scarcity of cobalt resources, the price of the positive electrode material LiCoO2 has remained high. The positive electrode material LiMO2 can achieve high energy density at a high nickel content, but as the nickel content increases, the structural stability of the material decreases, which in turn leads to severe capacity decay of lithium-ion batteries and unsatisfactory safety performance.
[0036] In recent years, the research and development direction of lithium-ion batteries has gradually shifted from single performance optimization to coordinated improvement of overall performance. Studies have shown that the mono- / binary composite cathode materials prepared by combining single cathode materials with other non-cathode materials or cathode materials can achieve complementary advantages, improve the electrochemical performance and cycle stability of the battery, and further reduce the cost of raw materials while maintaining or improving performance, which has very considerable application value.
[0037] However, the practical application of composite cathode materials still faces many challenges. Due to the significant differences in particle size, density and surface state of different material components, composite cathode materials show poor processing performance in the electrode sheet preparation process such as slurrying, coating and rolling. In addition, the overall performance of lithium-ion batteries depends not only on the characteristics of the components of the electrode slurry, such as the composition and properties of the active material, conductive agent and binder, but also highly depends on the migration and diffusion behavior of lithium ions in different cathode materials. The migration and diffusion abilities of lithium ions in lithium-ion batteries are different in different cathode materials, resulting in the inability of lithium ions to move quickly in different cathode materials, the uneven charge distribution on the surface of the cathode active material of lithium-ion batteries, and the easy precipitation of metal ions, which reduces the rate performance, cycle stability and high temperature performance of lithium-ion batteries. Therefore, how to optimize the preparation process of composite cathode slurry and cathode sheet processing technology, and enhance the rapid migration ability of lithium ions in composite cathode materials, is of great significance for promoting the practical application of composite cathode materials.
[0038] In view of the above problems, the embodiments of the present application provide a lithium-ion battery positive electrode additive, which can improve the processability of the positive electrode slurry and the positive electrode sheet of the lithium-ion battery, and enhance the rate performance, cycle stability and high temperature performance of the lithium-ion battery.
[0039] The technical solution of the embodiments of the present application is described in detail below with reference to the accompanying drawings.
[0040] An embodiment of the present application provides a positive electrode additive for a lithium ion battery, wherein the positive electrode additive includes a ferroelectric material coated with an ionic liquid; wherein a mass ratio of the mass of the ferroelectric material to the mass of the ionic liquid is m1, and 0.5≤m1≤100.
[0041] In one embodiment, the ferroelectric material and the ionic liquid can be weighed separately according to a set mass ratio; the ferroelectric material is placed in the ionic liquid in a rotating reactor, and the ferroelectric material and the ionic liquid are stirred and mixed in the rotating reactor, the stirring and mixing temperature is T, 60°C≤T≤200°C (degrees Celsius), and the stirring and mixing time is t, 4h≤t≤48h (hours); after the ferroelectric material and the ionic liquid are stirred and mixed evenly, the evenly mixed ferroelectric material and ionic liquid are centrifuged to obtain a colloidal precipitate, and the colloidal precipitate is dried to obtain a ferroelectric material coated with an ionic liquid; wherein, the mass ratio of the mass of the ferroelectric material to the mass of the ionic liquid in the ferroelectric material coated with an ionic liquid is m1, m1=(mass of the ferroelectric material) / (mass of the ionic liquid), 0.5≤m1≤100.
[0042] In one embodiment, the ferroelectric material may include but is not limited to BaTiO3 (barium titanate), (K, Na)NbO3 (potassium sodium niobate), PbZrTiO3 (lead zirconate titanate), (Bi 0.5 Na 0.5 )TiO3 (sodium bismuth titanate), Sr 1-x Ba x Nb2O6(barium strontium niobate), NaBa2Nb5O 15 (sodium barium niobate), Bi4Ti3O 12 (Bismuth titanate), CaBi4Ti4O 15 (Calcium bismuth titanate), SrBi4Ti4O 15 (bismuth strontium titanate) or one or more thereof.
[0043] In one embodiment, the ionic liquid may include, but is not limited to, one or more of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.
[0044] In one embodiment, the imidazolium ionic liquid may include but is not limited to one or more of 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium fluoride, 1-butyl-3-methylimidazolium fluoride, 1-allyl-3-methylimidazolium chloride, and 1-octyl-3-methylimidazolium hexafluorophosphate.
[0045] The positive electrode additive of the lithium ion battery of the embodiment of the present application includes a ferroelectric material coated with an ionic liquid. The ferroelectric material has a spontaneous polarization characteristic. Its unique crystal structure makes the positive and negative charge centers not overlap and produces an electric polarization intensity that is not equal to zero. The electric polarization intensity will be enhanced under external pressure or electric field conditions, and positively charged and negatively charged dipole ends will be formed on two opposite surfaces of the ferroelectric material, respectively. The dipole force of the positively charged and negatively charged dipole ends can promote the dispersion of positive electrode material particles with different properties (particle size, density, specific surface area, etc.) in the composite positive electrode material of the lithium ion battery through electrostatic repulsion, and at the same time form a steric hindrance to effectively prevent the aggregation and sedimentation of positive electrode material particles with different properties; the ionic liquid is in a molten state at room temperature, has a uniform charge distribution, good thermal stability, and has good compatibility with positive electrode material particles with different properties in the positive electrode slurry, can improve the compatibility between the ferroelectric material and the positive electrode material particles with different properties, and improve the suspension stability of the positive electrode slurry through its viscosity. Therefore, the positive electrode additive of the lithium-ion battery in the embodiment of the present application can improve and enhance the dispersion, uniformity and suspension stability of positive electrode material particles with different properties in the composite positive electrode material of the lithium-ion battery in the composite positive electrode slurry, so as to meet the requirements of subsequent coating of the positive electrode sheet and the requirements of the rolling process, and improve the processability of the composite positive electrode slurry and the positive electrode sheet of the lithium-ion battery.
[0046] Furthermore, the positive electrode additive of the lithium-ion battery in the embodiment of the present application includes a ferroelectric material coated with an ionic liquid. The ferroelectric material coated with an ionic liquid is extremely stable and can enable the positive electrode plate to have excellent and stable ion conductivity even under high temperature conditions. The built-in electric field generated by the spontaneous polarization of the ferroelectric material can enhance the migration and diffusion capabilities of lithium ions in the lithium-ion battery between positive electrode materials of different properties, and make the charge on the surface of the positive electrode active material evenly distributed, inhibit the precipitation of metal ions, and enhance the output performance of the lithium-ion battery, such as rate performance, cycle stability, safety, and high temperature performance.
[0047] Figure 1 It is a schematic flow chart of the method for preparing the positive electrode additive shown in the embodiment of the present application.
[0048] See also Figure 1 , a method for preparing a positive electrode additive, comprising:
[0049] Step 101, obtaining ferroelectric material and ionic liquid according to a set mass ratio.
[0050] Step 102, mixing the ferroelectric material and the ionic liquid in a rotating reactor according to set conditions to obtain a positive electrode additive for a lithium ion battery; wherein the positive electrode additive comprises a ferroelectric material coated with an ionic liquid, and the mass ratio of the mass of the ferroelectric material to the mass of the ionic liquid in the ferroelectric material coated with the ionic liquid is m1, 0.5≤m1≤100.
[0051] In one embodiment, the mass ratio is set as the mass ratio m2 of the mass of the ferroelectric material to the mass of the ionic liquid in the process of preparing the positive electrode additive, m2=mass of the ferroelectric material / mass of the ionic liquid, 0.1≤m2≤10. When preparing the ferroelectric material coated with the ionic liquid, adding an excess of ionic liquid can obtain a more uniformly coated positive electrode additive; but it is necessary to control the mass of the ionic liquid to avoid adding an excess of ionic liquid to increase the cost of preparing the lithium ion battery.
[0052] In one embodiment, the ferroelectric material and the ionic liquid of a set mass ratio can be mixed evenly in a rotating reactor under set conditions; the evenly mixed ferroelectric material and the excess ionic liquid in the ionic liquid are separated to obtain a colloidal precipitate; the colloidal precipitate is dried to obtain a positive electrode additive. The evenly mixed ferroelectric material and the excess ionic liquid in the ionic liquid are separated, and the excess ionic liquid after separation can be recycled to reduce the cost of preparing lithium-ion batteries.
[0053] In one embodiment, the ferroelectric material and the ionic liquid can be weighed separately according to a set mass ratio; the ferroelectric material is placed in the ionic liquid in a rotating reactor, and the ferroelectric material and the ionic liquid are stirred and mixed in the rotating reactor, the stirring and mixing temperature is T, 60°C≤T≤200°C, and the stirring and mixing time is t, 4h≤t≤48h; after the ferroelectric material and the ionic liquid are stirred and mixed evenly, the evenly mixed ferroelectric material and ionic liquid are centrifuged to separate the excess ionic liquid to obtain a colloidal precipitate, and the colloidal precipitate is dried to obtain a ferroelectric material coated with an ionic liquid; wherein, the mass ratio of the mass of the ferroelectric material to the mass of the ionic liquid in the ferroelectric material coated with an ionic liquid is m1, m1=(mass of the ferroelectric material) / (mass of the ionic liquid), 0.5≤m1≤100.
[0054] In one embodiment, the colloidal precipitate may be dried at a drying temperature of 60° C. to 120° C. for 6 h to 24 h to obtain a ferroelectric material coated with an ionic liquid.
[0055] In a specific embodiment, the ferroelectric material BaTiO3 can be added to the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, the mass ratio of the ferroelectric material BaTiO3 to the mass of the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt is 1:5, and the mixture is stirred and mixed in a rotating reactor for 24 hours, and the temperature of the reactor is controlled at 120°C; after uniform mixing, the mixture is centrifuged to obtain a colloidal precipitate, and the colloidal precipitate is dried to obtain the ferroelectric material BaTiO3 coated with the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.
[0056] The preparation method of the positive electrode additive of the embodiment of the present application comprises obtaining a ferroelectric material and an ionic liquid according to a set mass ratio; uniformly mixing the ferroelectric material and the ionic liquid in a rotating reactor according to set conditions to obtain a positive electrode additive for a lithium ion battery; the positive electrode additive for a lithium ion battery comprises a ferroelectric material coated with an ionic liquid, and the ferroelectric material coated with an ionic liquid can improve the dispersion, uniformity and suspension stability of positive electrode material particles with different properties (particle size, density, specific surface area, etc.) in a composite positive electrode slurry of a lithium ion battery, so as to meet the requirements of subsequent coating of a positive electrode sheet and the requirements of a rolling process, and can improve the processability of a positive electrode slurry and a positive electrode sheet of a lithium ion battery; the ferroelectric material coated with an ionic liquid can enhance the migration and diffusion capabilities of lithium ions of a lithium ion battery between positive electrode materials of different properties, and evenly distribute the charge on the surface of a positive electrode active substance, inhibit the precipitation of metal ions, and enhance the output performance of a lithium ion battery, such as rate performance, cycle stability and high temperature performance. The preparation method of the positive electrode additive of the embodiment of the present application will not significantly increase the production cost of the lithium-ion battery, and the process is simple and easy to implement, is environmentally friendly, and can more economically and effectively improve the processability of the positive electrode slurry and positive electrode sheet of the lithium-ion battery and enhance the output performance of the lithium-ion battery such as the rate performance, cycle stability and high temperature performance.
[0057] An embodiment of the present application provides a positive electrode plate for a lithium-ion battery, wherein the positive electrode plate includes the positive electrode additive described above, or includes the positive electrode additive prepared by the above preparation method.
[0058] In one embodiment, the positive electrode plate of the lithium-ion battery includes a positive electrode material and a positive electrode additive. The positive electrode material may include but is not limited to a composite positive electrode active material, a conductive agent, and a binder.
[0059] In one embodiment, the mass of the positive electrode additive of the positive electrode plate of the lithium ion battery is 0.001wt%-10wt% of the mass of the positive electrode material in the positive electrode plate; preferably, the mass of the positive electrode additive is 0.01wt%-2wt% of the mass of the positive electrode material in the positive electrode plate.
[0060] In one embodiment, the composite positive electrode active material of the positive electrode plate of the lithium-ion battery can be a mono- / binary composite positive electrode active material prepared by combining a single positive electrode active material with other non-positive electrode active materials or positive electrode active materials.
[0061] In one embodiment, the composite positive electrode active material, the conductive agent, the binder, and the positive electrode additive can be evenly mixed to prepare a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector; and then dried, rolled, and cut into pieces to obtain a positive electrode plate of a lithium ion battery; wherein the mass of the ferroelectric material coated with the positive electrode additive ionic liquid is 0.01wt%-2wt% of the mass of the positive electrode material in the positive electrode plate.
[0062] An embodiment of the present application also provides a lithium-ion battery, which includes the above-mentioned positive electrode plate.
[0063] In one embodiment, a lithium-ion battery may include a battery housing, a separator, an electrolyte, a negative electrode plate, and the positive electrode plate described above; wherein the positive electrode plate of the lithium-ion battery includes a positive electrode additive.
[0064] In one embodiment, the battery housing, diaphragm, electrolyte, and other materials of the negative electrode plate and the positive electrode plate of the lithium-ion battery can all adopt existing conventional structures and materials.
[0065] The following is further described by specific comparative examples 1-2 and embodiments 1-14.
[0066] The composite positive electrode active material of Comparative Examples 1-2 and Examples 1-14 includes 60 wt % LiCoO2, 40 wt % LiNi 0.8 Co 0.1 Mn 0.1 O2, the conductive agent includes conductive carbon black and carbon nanotubes, the binder includes polyvinylidene fluoride, the mass ratio of the composite positive electrode active material, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride is 96:1:(0.6):(2.4), and the solvent is N-methylpyrrolidone. When preparing the positive electrode slurry, the binder can be prepared into a glue solution with a solid content of 5wt% to 9wt%, the composite positive electrode active material, the positive electrode additive (when the positive electrode additive is required) and the conductive carbon black are stirred at a low speed and mixed evenly, and then the glue solution, carbon nanotubes and N-methylpyrrolidone are added to knead and disperse at a high speed, and finally vacuum defoaming is performed to obtain the positive electrode slurry; after the positive electrode slurry is coated on the positive electrode collector (aluminum foil), it is baked, rolled, and cut to obtain the positive electrode sheet of the lithium ion battery.
[0067] The positive electrode sheets, graphite negative electrode sheets, separators and electrolytes of Comparative Examples 1-2 and Examples 1-14 are assembled into soft-pack lithium-ion batteries. The models and specifications of the soft-pack lithium-ion batteries of Comparative Examples 1-2 and Examples 1-14 are the same, except for the positive electrode sheets of the lithium-ion batteries. The specific differences between Comparative Examples 1-2 and Examples 1-14 are shown in Table 1-4. The slurry viscosity, suspension stability after 12h, suspension stability after 24h, and suspension stability after 48h of the positive electrode slurries of Comparative Examples 1-2 and Examples 1-14, as well as the sheet flexibility, peel strength (N / m), membrane resistance (Ω*cm), and processing comprehensive score (points) of the positive electrode sheets of Comparative Examples 1-2 and Examples 1-14 are evaluated respectively. The electrochemical performance tests of the soft-pack lithium-ion batteries of Comparative Examples 1 and Examples 1-5 are performed respectively to obtain the data shown in Table 1-4; wherein,
[0068] The slurry viscosity of the positive electrode slurry is the viscosity obtained by measuring the positive electrode slurry using a rotational viscometer.
[0069] The suspension stability of the positive electrode slurry after 12 hours, 24 hours and 48 hours is measured by placing the positive electrode slurry in a 200ml beaker for 12 hours, 24 hours and 48 hours respectively, and then testing the change in solid content of the upper and lower layers. If the solid content of the upper layer decreases by more than 2% and the solid content of the lower layer increases by more than 2%, it means that the positive electrode slurry has settled.
[0070] The flexibility of the positive electrode sheet is determined by folding the rolled positive electrode sheet 180° to observe its light transmittance and brittle fracture conditions. The more folds the sheet is made and the less light transmittance it has, the better the flexibility.
[0071] The peel strength (N / m, Newton per meter) test of the positive electrode sheet is the bonding strength between the positive electrode coating and the positive electrode collector after rolling. It can be tested using a tensile testing machine. The larger the peel strength value, the better the peel strength.
[0072] The diaphragm resistance (Ω*cm, ohm centimeter) of the positive electrode sheet can be tested by using a resistance meter on the rolled positive electrode sheet to obtain the diaphragm resistance of the positive electrode sheet. The smaller the diaphragm resistance value, the better the conductivity of the positive electrode sheet.
[0073] The comprehensive processing score (points) of the positive electrode plate is used to comprehensively evaluate the processing performance of the slurry processing, coating, and rolling of the positive electrode plate. In the comparative examples 1-2 and embodiments 1-14 of the present application, the full score of the comprehensive processing score of the positive electrode plate is 5 points. 1 point is deducted if the slurry viscosity of the positive electrode plate is too high or too low. 0.5 point is deducted for slight sedimentation after 12 hours, 24 hours, and 48 hours, and 1 point is deducted for sedimentation. The flexibility of the positive electrode plate is slightly translucent if two folds are folded, and 1 point is deducted for light translucency if one fold is folded. The peel strength of the positive electrode plate is less than 30 N / m, and 0.5 point is deducted, and 1 point is deducted if it is less than 20 N / m. The membrane resistance is greater than 40 Ω*cm, and 0.5 point is deducted, and greater than 50 Ω*cm, and 1 point is deducted. The processing performance of the positive electrode plates of comparative examples 1-2 and embodiments 1-14 is comprehensively scored.
[0074] The electrochemical performance tests of the soft-pack lithium-ion batteries of Comparative Example 1 and Examples 1-5 shown in Table 2 include 0.2C rate discharge performance, 0.5C rate discharge performance, 1C rate discharge performance, room temperature cycle performance, and 45°C cycle performance. The 0.2C rate discharge performance, 0.5C rate discharge performance, and 1C rate discharge performance are the discharge test data of the soft-pack lithium-ion batteries of Comparative Example 1 and Examples 1-5 at different discharge rates (0.2C, 0.5C, and 1C) at constant temperature.
[0075] The room temperature cycle performance refers to the capacity retention rate of the soft-pack lithium-ion batteries of Example 1 and Examples 1-5 at room temperature (25° C.) and 0.5C charge and discharge cycle test for 400 cycles.
[0076] The 45°C cycle performance refers to the capacity retention rate of the soft-pack lithium-ion batteries of Example 1 and Examples 1-5 when the battery is charged and discharged at 45°C and 0.5C for 400 cycles.
[0077] Table 1:
[0078]
[0079] Table 2:
[0080]
[0081] Table 3:
[0082]
[0083] Table 4:
[0084]
[0085] According to the data of Table 1 Comparative Example 1 and Examples 1-5, the positive electrode plates of Examples 1-5 are added with positive electrode additives (ferroelectric materials coated with ionic liquids), and the positive electrode additives have a dispersing effect on the composite positive electrode active materials, conductive agents, etc. in the positive electrode slurry. The positive electrode additives form steric hindrances through polarity in the positive electrode slurry, which can effectively prevent the aggregation and sedimentation of the positive electrode material solid particles with different properties (particle size, density, specific surface area, etc.) in the composite positive electrode material, and improve the suspension stability of the positive electrode slurry. The positive electrode additives can improve the dispersion, uniformity and suspension stability of the positive electrode material particles with different properties in the composite positive electrode material in the composite positive electrode slurry, thereby reducing the positive electrode The viscosity of the slurry improves the fluidity of the positive electrode slurry, making the positive electrode slurry more in line with the coating requirements; at the same time, since the dispersion, uniformity and suspension stability of the positive electrode material particles with different properties in the composite positive electrode slurry are improved, the prepared positive electrode pole sheet has better flexibility; the viscosity of the ionic liquid in the positive electrode additive can improve the peel strength of the positive electrode pole sheet; the uniform distribution of the composite positive electrode active material and the conductive agent in the positive electrode slurry reduces the membrane resistance of the positive electrode pole sheet; therefore, the positive electrode additive comprising a ferroelectric material coated with an ionic liquid in the embodiment of the present application can more economically and effectively improve the processability of the positive electrode slurry and positive electrode sheet of the lithium-ion battery.
[0086] According to the data of Comparative Example 1 and Examples 1-5 in Table 2, positive electrode additives (ferroelectric materials coated with ionic liquids) are added to the positive electrode plates of Examples 1-5. The positive electrode additives enhance the migration and diffusion capabilities of lithium ions of lithium-ion batteries between positive electrode materials of different properties, and evenly distribute the charges on the surface of the positive electrode active material, inhibit the precipitation of metal ions, and enable the positive electrode plates to have excellent and stable ion conduction capabilities even at high temperatures, thereby enhancing the output performance of lithium-ion batteries, such as rate performance, cycle stability, and high temperature performance.
[0087] According to the data of Example 1 in Table 1, Comparative Examples 1-2 in Table 3 and Examples 6-9, the increase of the ionic liquid used in preparing the positive electrode additive can make the ionic liquid more evenly include the ferroelectric material, can better improve the dispersion, uniformity and suspension stability of positive electrode material particles with different properties in the composite positive electrode slurry, and better improve the processability of the positive electrode sheet of the lithium ion battery.
[0088] According to the data of Comparative Example 1 in Table 1 and Examples 10-14 in Table 4, after the mass of the ferroelectric material (positive electrode additive) coated with the ionic liquid is greater than 2wt%, continuing to increase the mass of the ferroelectric material (positive electrode additive) coated with the ionic liquid does not effectively improve the dispersion, uniformity and suspension stability of the positive electrode material particles with different properties in the composite positive electrode slurry, that is, it does not effectively improve the processability of the positive electrode sheet of the lithium ion battery.
[0089] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A positive electrode additive for a lithium ion battery, characterized in that: Comprising a ferroelectric material coated with an ionic liquid; wherein, The mass ratio of the mass of the ferroelectric material to the mass of the ionic liquid is m1, and 0.5≤m1≤100.
2. The positive electrode additive according to claim 1, characterized in that: The ferroelectric materials include BaTiO3 (barium titanate), (K, Na)NbO3, PbZrTiO3, (Bi 0.5 Na 0.5 )TiO3、Sr 1- x Ba x Nb2O6、NaBa2Nb5O 15 、Bi4Ti3O 12 、CaBi4Ti4O 15 、SrBi4Ti4O 15 One or more of .
3. The positive electrode additive according to claim 1 or 2, characterized in that: The ionic liquid includes one or more of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.
4. The positive electrode additive according to claim 3, characterized in that: The imidazolium ionic liquid includes one or more of 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium fluoride, 1-butyl-3-methylimidazolium fluoride, 1-allyl-3-methylimidazolium chloride, and 1-octyl-3-methylimidazolium hexafluorophosphate.
5. A method for preparing a positive electrode additive, characterized in that: include: Obtain ferroelectric materials and ionic liquids according to a set mass ratio; The ferroelectric material and the ionic liquid are mixed uniformly in a rotating reactor according to set conditions to obtain a positive electrode additive for a lithium ion battery; wherein, The positive electrode additive comprises a ferroelectric material coated with an ionic liquid, wherein the mass ratio of the mass of the ferroelectric material to the mass of the ionic liquid in the ferroelectric material coated with the ionic liquid is m1, and 0.5≤m1≤100.
6. The preparation method according to claim 5, characterized in that: The set mass ratio is the mass ratio m2 of the mass of the ferroelectric material to the mass of the ionic liquid during the preparation of the positive electrode additive, 0.1≤m2≤10.
7. The preparation method according to claim 5, characterized in that: The method of uniformly mixing the ferroelectric material and the ionic liquid in a rotating reactor according to set conditions to obtain a positive electrode additive for a lithium ion battery comprises: The ferroelectric material and the ionic liquid are uniformly mixed in a rotating reactor according to set conditions; separating the uniformly mixed ferroelectric material and the excess ionic liquid in the ionic liquid to obtain a colloidal precipitate; The colloidal precipitate is dried to obtain the positive electrode additive.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The setting conditions include mixing temperature T, and / or mixing time t; wherein, 60℃≤T≤200℃; 4h≤t≤48h.
9. A positive electrode plate for a lithium-ion battery, characterized in that: The invention comprises the positive electrode additive as described in any one of claims 1 to 4, or comprises the positive electrode additive prepared by the preparation method as described in any one of claims 5 to 8.
10. The positive electrode sheet according to claim 9, characterized in that: The mass of the positive electrode additive is 0.001wt%-10wt% of the mass of the positive electrode material in the positive electrode sheet; Preferably, the mass of the positive electrode additive is 0.01wt%-2wt% of the mass of the positive electrode material in the positive electrode sheet.
11. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as described in claim 9 or 10.
